Assessment and Analysis of the Various Electrical System Configurations Used to Power BTS Sites in Benin - CHETANGNY, Patrice Koffi; ZOGBOCHI, Victor; TCHIKE, M. Sylvain; HOUNNOU, Hypolite Jordao; Aredjodoun, Jacques G.; HOUNDEDAKO, SOSSOU; BARBIER, Gérald; CHAMAGNE, Didier (My University, 2023)
This article presents the different configurations of electrical power systems used to supply Base Transceiver Stations (BTS) sites in Benin. The technical, economic, and environmental performance of each system was also studied and analysed. The results of these studies and analyses showed that mobile phone operators in Benin mostly use four types of electrical power system configurations for BTS sites, namely DG/Grid, DG/Grid/Battery, DG/Battery, and DG/DG. The consumption analysis of combined 2G+ 3G+4G technology sites was also addressed. The study found that site consumption varies depending on traffic and that subscribers are much more active during the day than at night. The average monthly consumption per site for combined 2G+ 3G+4G technology sites ranges from 1807 kWh to 5767 kWh with an average of 3537 kWh. The technical, economic, and environmental analysis of the four configurations showed that configurations that integrate the electrical grid are economically efficient and less polluting than configurations that only use diesel generators.
Keywords: Economics; GSM; Wind energy generation; Renewable energy sources; Power supplies; Cellular phones; Optimized production technology